PET/MRI, aiming to improve the target for Fractionated Stereotactic Radiotherapy (FSRT) in recurrence of resected skull base meningioma after 2 years: Case report - Corrêa, Sebastião (Archives of Case Reports, 2021)
The increasing use of highly conformal radiation deliberates a higher accurate targeting. Contouring and clinical judgment are presumably the crucial point, thus positron emission tomography/magnetic resonance imaging PET/MRI with somatostatin analogs appears to be useful in radiotherapy target definition. A case report of a 43-year-old woman presented with a recurrence of a meningioma (World Health Organization group I classification) in skull base, 2 years after resection. Magnetic resonance imaging (MRI) revealed a left sided skull base mass on sphenoid wing, anterior clinoid and with a soft tissue component in the lateral portion of the orbit. Contrast-enhanced MRI and a computed tomography (CT) dedicated were used to the radiotherapy planning. Aiming an improvement on target volume delineation, 68Ga-DOTATOC-PET/MRI was also performed due the difficult localization of the tumor in skull base. Was treated using intensity-modulated radiotherapy (IMRT) to a total dose of 54 Gy in 28 fractions. It was prescribed to the planning target volume (PTV), defined based of both imaging modalities. In our case PET/MRI helped to define the target, which volume becomes bigger than that based exclusively on MRI and CT.